Correlation Between Self-Regulation and Children’s Readiness to Enroll Primary School - Faqumala, Dwi Anisa; Suminar, Tri; Pranoto, Yuli Kurniawati Sugiyo (Journal of Primary Education, 2020)
This research aims to find out correlations of self-regulation to childrenÃ¢â‚¬â„¢s readiness in enrolling primary school. This quantitative research used associative method. The population consisted 5,284 children aged 5-6 year old in Semarang municipal. The techniques of sampling used multistage random sampling. There were 220 children consisting of 110 male and 110 female children. The technique to collect the data was questionnaire in which the filling system was read aloud by the researcher as assistance. Self-regulation was measured by Head-Toes-Knees-Shoulders (HTKS) task. Meanwhile, the readiness was measured by readiness scale to enroll primary school. The hypothesis test used regression test. The results showed that tÃ‚Âcount=1.847 > ttable =1.651. The sig score was 0.006<0.05. It meant there was correlation of self-regulation to childrenÃ¢â‚¬â„¢s readiness to enroll primary school. Then, the effects of sex types as moderating variable with P = 0.709, larger than 0.05, showing that there was no difference in male self-regulation and female self-regulation to their readiness in enrolling primary school. Thus, it could be concluded that self-regulation influenced the childrenÃ¢â‚¬â„¢s readiness to enroll primary school. However, both male and female children, they did not have significant difference. Thus, parents, teachers, and governments should cooperate in preparing children enrolling primary school level not only in term of childrenÃ¢â‚¬â„¢s readiness aspect but also the external aspect, such as parentsÃ¢â‚¬â„¢ readiness and school readiness.